The Influence Of The Quality Of Human Resources, Computer Devices, Leadership Style, And Organizational Commitment On Government Accounting Standards In Garut Regency - Putri, Marissa Disthy; Merliyana, Reny Dany (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the effect of the quality of human resources, the adequacy of accounting computer equipment, leadership style, and organizational commitment to implementing accrual-based government accounting standards in the government of Garut Regency. This study uses a quantitative approach with data analysis tools using multiple linear regression analysis, using the SPSS version 16 application assistance. The data source of this study uses primary data. The data collection of this research used a questionnaire with 93 respondents and a sample of 31 SKPD of the Garut Regency Government. The results of this study indicate that partially the variables of the quality of human resources, the adequacy of accounting computer equipment, leadership style, and organizational commitment affect the implementation of accrual- based government accounting standards in the government of Garut Regency. Keywords: Quality of Human Resources, Adequacy of Accounting Computer Equipment, Leadership Style, Organizational Commitment, and Accrual-Based SAP Implementation